Antihyperglycemic Activity of Extracts from Boldoa purpurascens Leaves in Alloxan‐Induced Diabetic Rats. (17th July 2012) - González Mosquera, D. M.; Hernandez Ortega, Y.; By, B.; Vicet Muro, L.; Saucedo Hernandez, Y.; Grau Ábalos, R.; Dehaen, W.; Pieters, L.; Apers, S.
<x xml:space="preserve">Abstract</x> In order to investigate the potential use of Boldoa purpurascens against diabetes, the antihyperglycemic effect of an ethanol extract obtained from its leaves was evaluated at doses of 50, 100 and 200 mg/kg in rats after induction of hyperglycemia by alloxan. Insulin 5 IU/kg was used as positive control and NaCl 0.9% as negative control. A similar experiment was performed with the aqueous extract used at doses of 50 and 100 mg/kg using metformin at a dose of 50mg/kg as positive control. Statistical analysis was carried using the Kruskal–Wallis test with an interval of trust of 99%. The ethanolic and aqueous extract of B. purpurascens showed a significant decrease of blood glucose levels 72 h after administration. Phytochemical analysis of the ethanol extract showed the presence of D‐pinitol, a compound known for its hypoglycemic properties. In conclusion, ethanolic as well as aqueous extracts of B. purpurascens leaves show antihyperglycemic activity, possibly due to the presence of D‐pinitol and flavonoids. Copyright © 2012 John Wiley & Sons, Ltd.